Gambaran Faktor Risiko Obesitas Sentral Pada Masyarakat di Puskesmas Mon Geudong Kota Lhokseumawe - M. Fashanul Fathan Kamal; Cut Sidrah Nadira (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia faces various nutritional problems, one of which is central obesity. This condition occurs due to excessive energy intake that surpasses the amount of energy used for metabolism and daily activities. The excess energy is stored as fat tissue, which eventually leads to weight gain and increases the risk of various metabolic diseases. This study aims to examine the risk factors for central obesity in the community at Mon Geudong Public Health Center, Lhokseumawe City.This study employs a descriptive observational method with a cross-sectional survey design. The population consists of 1,121 individuals, and the sample was obtained using a non-probability sampling technique with accidental sampling, resulting in a total of 100 respondents. Data collection was conducted through questionnaires and waist circumference measurements using a measuring tape. Data were analyzed using univariate analysis to examine the distribution of respondent characteristics.The results indicate that the most affected age group is 56–65 years (49.0%). Based on gender, more women (80.0%) experience central obesity compared to men (20.0%). The majority of respondents are unemployed, possess good knowledge levels, and 69.0% have a family history of central obesity.The study concludes that the primary risk factors for central obesity include age, gender, occupation, and family history. However, knowledge level is not considered a risk factor for central obesity. This research is expected to serve as a basis for central obesity prevention efforts through education and the promotion of a healthy lifestyle in the community.